2006
DOI: 10.1063/1.2390641
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of a platinum target in water. II. Ablation rate and nanoparticle size distributions

Abstract: This is the second in a series of three papers examining nanomaterial formation in laser ablation in liquids (LAL). Here we study the effect of the laser wavelength and fluence on the mass yield and size distribution of nanoparticles prepared by laser ablation of a platinum target immersed in water. For all wavelengths tested, laser fluences in the range of 10–70J∕cm2 resulted in spheroidal, nonagglomerated platinum nanoparticles with sizes ranging from 1to30nm. Nanoparticle size distributions are found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 25 publications
9
112
2
Order By: Relevance
“…The NP size distributions described above are in consonance with previous studies of laser ablation of platinum in water using the wavelengths of 1064, 532 and 355 nm, although the laser fluences (11-65 J cm -2 ) used were significantly greater than those applied here. 36 In those studies, similarly broad and bimodal NP size distributions were observed, also narrowing down and shifting to smaller sizes with decreasing wavelength. The two components of the NP size distribution were plausibly traced back to a thermal vaporization mechanism (small NP component) and to an explosive ablation mechanism (large NP component) taking place in different time scales.…”
Section: Characterization Of the Nanoparticles Produced By Laser Ablamentioning
confidence: 77%
See 3 more Smart Citations
“…The NP size distributions described above are in consonance with previous studies of laser ablation of platinum in water using the wavelengths of 1064, 532 and 355 nm, although the laser fluences (11-65 J cm -2 ) used were significantly greater than those applied here. 36 In those studies, similarly broad and bimodal NP size distributions were observed, also narrowing down and shifting to smaller sizes with decreasing wavelength. The two components of the NP size distribution were plausibly traced back to a thermal vaporization mechanism (small NP component) and to an explosive ablation mechanism (large NP component) taking place in different time scales.…”
Section: Characterization Of the Nanoparticles Produced By Laser Ablamentioning
confidence: 77%
“…Hence, the shoulder observed around 250 nm in the UV absorption spectra could be attributed to plasmonic excitation, possibly partially overlapping with interband transitions. 36,38 We did not observe potential plasmonic bands better defined than those shown in Figure 1 for any of the samples. This is not surprising given the small size and appreciable polydispersity of the NPs produced by the ablation method, as discussed below.…”
Section: Characterization Of the Nanoparticles Produced By Laser Ablamentioning
confidence: 78%
See 2 more Smart Citations
“…The use of high-power picosecond pulses was successfully demonstrated by Bärsch et al for the ablation of various materials in liquids [25]. (iii) Several research groups have found that for nanosecond pulses the yield of nanoparticles was significantly higher for ablation using the fundamental wavelength (λ = 1064 nm) than for second or third harmonic wavelength (λ = 532 nm or 355 nm) [26][27][28]. Procházka et al demonstrated that an increasing number of irradiating nanosecond laser pulses using a laser wavelength of 1064 nm results in a decrease of the particle size in silver colloids [8].…”
Section: Introductionmentioning
confidence: 99%